Viral load dynamics among adults receiving HIV care in rural North-Eastern South Africa, 2015–2020: insights from a population-based record linkage study - Dzomba, Armstrong; Gomez-Olive, Francesc Xavier; Bashingwa, Jean; Sibanda, Morelearnings; Njiro, Belinda; Kahn, Kathleen; Ohene-Kwofie, Daniel; Kabudula, Chodziwadziwa (Frontiers in Public Health, 2025)
IntroductionThe Joint United Nations Programme on HIV/AIDS set ambitious-but-reachable targets to have 95% of HIV-positive people diagnosed, 95% on ART, and 95% virally suppressed by 2030. To address the latter, post-2016, South Africa’s HIV treatment guidelines aimed to deliver maximal and durable viral load (VL) suppression through extensive antiretroviral therapy (ART) scale-up. Yet, standard suppression one-off measurement conceals viral response trajectories with high onward transmission potential for HIV patients on lifelong treatment. We investigated the dynamics of periodic VL patterns and associated socio-demographic factors in rural north-eastern South Africa using data from adults receiving HIV care in healthcare facilities within the Agincourt Health and Demographic Surveillance System (HDSS).MethodsWe extracted two person-identified VL measurements collected 9-15 months apart per individual yearly between 2015 and 2020 from the Agincourt HDSS Hospital-Clinic-Linkage system for 7 493 HIV patients. Sankey diagrams were used to describe VL flows within and across the suppressed and unsuppressed statuses over each year. We classified temporal VL responses into four profiles: (i) Sustained suppression, (ii) achieved suppression, (iii) viral rebound, (iv) virologic failure. Additionally, mixed-effects multinomial logistic regression models were utilised to examine the odds of covariates factors for varied VL trajectories.ResultsThe proportion of individuals remaining virally suppressed increased steadily from 84% in 2015 to 86% in 2016, with the highest prevalence of 88% sustained for three consecutive years, from 2017 through 2019, and then dropped slightly in 2020 to 87%. However, 2-3% of initially virally suppressed rebounded annually, while ~5% experience treatment failure. The likelihood of achieving viral suppression was high among men, those aged 15-24 years and 25-34 years however, these groups were less likely to have sustained viral suppression and more likely to experience virologic failure and rebounding.ConclusionsTemporal VL metrics are needed to effectively track progress towards reaching high and sustained HIV suppression potential in HIV hyperendemic settings. Thus, optimising the assessment of targeted interventions and identification of left-behind groups such as those younger, men, unmarried and poorer HIV patients to improve individual and population health outcomes.